Analisis Tingkat Kepuasan Pelanggan Terhadap Kualitas Pelayanan Delifa Space Self-Photo Studio Kabupaten Sidenreng Rappang - Malik Fajar; Muhammad Tamrin; Haslindah; Andi Riska Andreani Syafaruddin (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The Self-Photo studio industry is growing rapidly along with the increasing trend of instant photography and customer demand for a more personalized photo experience. Delifa Space Self-Photo Studio needs to understand the level of customer satisfaction to improve its services. This study analyzes customer satisfaction with service quality at Delifa Space using the SERVQUAL approach. The quantitative method is applied with a questionnaire distributed to 73 respondents, determined using the Slovin formula with a 10% error tolerance. Data were analyzed using IBM SPSS Statistics V22 through validity, reliability, normality, and simple linear regression tests. The results showed that service quality has a significant effect on customer satisfaction (Sig. <0.05), with physical evidence and reliability dimensions as the main factors. Customers consider physical facilities and service consistency more in assessing their experiences. However, aspects such as the variety of photo props, flexible reservation systems, and the comfort of the studio space still need to be improved. Delifa Space is advised to improve the studio layout, lighting, variety of photo props, and ensure the timeliness of service, consistency of shooting procedures, and staff responsiveness to increase customer satisfaction and loyalty.